Conceptual metaphor in Argentinian political discourse (based on the speech of the Argentinean President (2007–2015) C.Fernández de Kirchner during the 69th session of the UN General Assembly) - I. S. Vorontsova (Ибероамериканские тетради, 2019)
The article reviews the history of discourse analysis development. The definitions of the terms discourse, political discourse and metaphor are given. The main contemporary European and Russian linguistic approaches to metaphor study are analyzed. The article also presents the analysis of the conceptual metaphor types (orientational, ontological, structural) in the political discourse, as well as its functions according to the cognitive approach. The metaphor nominating different socio-political actions and phenomena on the basis of the cognitive world picture is an integral part of the modern political discourse and contains vast imaginative and notional potential, the skillful usage of which helps the orator to carry out their speech intentions. The speech given by the Argentinean President (2007–2015) K. Fernández de Kirchner during the 69th session of the UN General Assembly has become the material for the study.